Pemberian Konseling Individu untuk Menurunukan Burnout Belajar Siswa Kelas VII MTs Al-Ma’arif - Luluk Setyawati; Arifin Nur Budiono (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2019)
This study aims to reduce the intensity of learning burnout through individual counseling. The research was conducted at Mts Al-Ma'arif and obtained data about 56% or more than half of the existing students experienced learning burnout. The type of research used is action research guidance and counseling (PTBK). The procedure used is the cycle model. Based on the results of the research, the first cycle of the first meeting of respondents still shows the attitude of learning burnout. It is shown from student activeness, student interest, student enthusiasm, and conducive student only ranged between 60-66%. The second meeting, respondents have shown a better situation that is about 78%. The first cycle of the first meeting, about 80%. The second meeting, student activity, student interest, student enthusiasm, and conducive students increased, ranging from 89-91%. Thus it can be concluded that Counseling individual can decrease the learning burnout. Keywords: Learning Burnout, Counseling individual.